2020
DOI: 10.1016/j.vaccine.2020.03.035
|View full text |Cite
|
Sign up to set email alerts
|

No association between HPV vaccination and infertility in U.S. females 18–33 years old

Abstract: Background-Human papillomavirus (HPV) vaccines have been recommended as primary prevention of HPV-related cancers for over 10 years in the United States, and evidence reveals decreased incidence of HPV infections following vaccination. However, concerns have been raised that HPV vaccines could decrease fertility. This study examined the relationship between HPV immunization and self-reported infertility in a nationally representative sample. Methods-Data from the 2013-2016 National Health and Nutrition Examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Despite this, menstruation is seldom considered a variable during vaccine trials aside from determining last menstrual period as part of established protections against volunteers being or getting pregnant. The vast majority of research that has been conducted regarding reproductive and menstrual function centers around whether or not live and attenuated vaccines are safe to give someone who is pregnant (61)(62)(63)(64), or if it affects fertility (65,66). The research that has been conducted on menstrual cycles specifically is often not able to establish a causal link, as the data is obtained through retrospective surveys or data mining (67,68) and randomized controlled trials often do not allow a mechanism for reporting these changes (44).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, menstruation is seldom considered a variable during vaccine trials aside from determining last menstrual period as part of established protections against volunteers being or getting pregnant. The vast majority of research that has been conducted regarding reproductive and menstrual function centers around whether or not live and attenuated vaccines are safe to give someone who is pregnant (61)(62)(63)(64), or if it affects fertility (65,66). The research that has been conducted on menstrual cycles specifically is often not able to establish a causal link, as the data is obtained through retrospective surveys or data mining (67,68) and randomized controlled trials often do not allow a mechanism for reporting these changes (44).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent cross-sectional study of survey data evaluated HPV vaccination and the rate of self-reported infertility and found no association. 20 Although this is a reassuring result, the highly heterogeneous nature of infertility and the cross-sectional design preclude this study from adding significantly to the evidence on HPV vaccination and the rate of primary ovarian insufficiency.…”
Section: Discussionmentioning
confidence: 95%
“…Este divulga informações pseudocientíficas que comprometem à segurança das vacinas 21 . Concepções que após a administração da 4vHPV pode causar efeitos colaterais como infertilidade e até mesmo levar a morte não possui veracidade científica 22,23 . Eventos como tontura, desmaio e dores locais são efeitos psicogênicos que ocorrem quando um indivíduo é vacinado em conjunto presenciando reações de outros no recebendo da vacina.…”
Section: Discussionunclassified